2001
DOI: 10.2223/jped.203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perinatal Asphyxia on Thyroid Hormones

Abstract: ResumoObjetivo: verificar o efeito da asfixia perinatal sobre os hormô-nios tireóideos.Métodos: foi realizado um estudo de caso-controle, no hospital de Clínicas de Porto Alegre, envolvendo 17 recém-nascidos a termo asfixiados (A) e 17 não-asfixiados (N), pareados conforme a cor, sexo, tipo de parto, idade gestacional e peso de nascimento. Foram coletados T4, T3, T4 livre, T3 reverso e TSH do sangue do cordão e do recém-nascido com 18 a 24 horas de vida, entre os que sofreram ou não asfixia perinatal.Resultado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
3
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
5
3
1
Order By: Relevance
“…Similar results were observed by Pereira DN et al, 6 Borges et al 7 observed that mean value of FT3, and FT4 levels were significantly lower at 24 hrs and 48 hrs in the asphyxiated group than the control group but the mean levels of TSH were similar. In contrast to all studies, Franklin R C et at, 4 found no significant correlation in birth asphyxia and thyroid profile in newborn.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar results were observed by Pereira DN et al, 6 Borges et al 7 observed that mean value of FT3, and FT4 levels were significantly lower at 24 hrs and 48 hrs in the asphyxiated group than the control group but the mean levels of TSH were similar. In contrast to all studies, Franklin R C et at, 4 found no significant correlation in birth asphyxia and thyroid profile in newborn.…”
Section: Discussionsupporting
confidence: 87%
“…These finding were comparable to Borges et at al, 7 and Pereira DN et al 6 whereas Thivoric HF 3 found that mean value of T 3 andT4 were significantly lower in cord blood of asphyxiated newborns compared to healthy term babies.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our observations are similar to study done by Pereira et al; [11] they had 17 cases of birth asphyxia and 17 controls. The median value of S.T3 between 18-24 hours of life in controls were 164.00 (56.96-222.5) ng/dl as compared to 40.8(37.4-80.4) ng/dl in cases (P= 0.003).The Mean value of S.FT4 level in cases was 1.85± 0.92 ng/dl as compared to 2.8± 0.74 U/L in the control group (P = 0.004).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are similar to Pereira et al; [11] they found that hormone alterations were more frequent in neonates presenting with moderate/severe hypoxicischemic encephalopathy. They compare asphyxiated babies with and without moderate/severe encephalopathy with control group, and found that asphyxiated babies with moderate/severe encephalopathy presented a significantly lower FT4 mean (1.44±0.63ng/dl) than those without disease (2.81±0.74ng/dl).…”
Section: Discussionsupporting
confidence: 92%